Body composition in rhythmic gymnasts of different competition program - Purenovic-Ivanovic, T.; Popovic, R.; Moskovljevic, L.; Pencic, N. (XX Scientific Conference in physical education, sport and recreation - (Nis, Serbia, october 19-21st, 2017) - Book of Proceedings, 2017)
The main objective of this study was to examine the body composition profile of rhythmic gymnasts competing in different programs, as well as to determine possible differences between them. The sample consisted of 254 club , national and international level gymnasts, distributed in five age group categories (25 seniors, aged 16 years and older; 39 juniors, aged 14-16 years; 50 advanced, aged 12-14 years; 83 intermediate, aged 9-12 years; 57 beginners, aged six to nine years) and three competition programs ("A" program, N=84; "B" program, N=101; "C" program, N=69). Their baseline characteristics (age, body height, body mass, body mass index, years of training experience, training hours) were established, as well as their body composition profile (BF% body fat percentage and Muscle% muscle mass percentage). By means of One way ANOVA, statistically significant differences in body composition of "A", "B" and "C" advanced and intermediate level gymnasts and beginners were established (BF%: F=12.84, p=0.000; F=17.77, p=0.000; F=5.97, p=0.005, respectively; Muscle%: F=7.63, p=0.001; F=17.69, p=0.000; F=5.10, p=0.009, respectively). The differences in body composition were missing in the group of senior and junior RGs, as well as between "A" and "B" intermediate level gymnasts and between "B" and "C" beginners. Also, neither were established statistically significant differences in Muscle% between "A" and "B" advanced level gymnasts and beginners, nor between "B" and "C" advanced level gymnasts.